1994
DOI: 10.2172/10163800
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of application of calcination/dissolution to the Hanford tank waste inventory

Abstract: Approximately 330,000 motric tons of sodium-rich radioactive waste originating from separation of plutonium from irradiated uranium fuel are stored in underground tanks at the U.S. Department of Energy (DOE) Hanford Site in Washington State. Fractionation of the waste into low-level waste (LIN) and high-level waste (HLW) streams is envisioned via partial water dissolution and limited radionuclide extraction operations. Under optimum conditions, LLWwould contain most of the chemical bulk while HLWwould contain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 4 publications
4
25
0
Order By: Relevance
“…Decontamination and treatment of radioactive waste accumulated during industrial production of plutonium for military use in both the United States and Russia is an important subject of investigation and research (Walton 1979, Harmon 1994, Delegard et al 1994. Processing and disposing of Hanford Site high-level waste (HLW) is part of the problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decontamination and treatment of radioactive waste accumulated during industrial production of plutonium for military use in both the United States and Russia is an important subject of investigation and research (Walton 1979, Harmon 1994, Delegard et al 1994. Processing and disposing of Hanford Site high-level waste (HLW) is part of the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Processing and disposing of Hanford Site high-level waste (HLW) is part of the problem. This waste is made up of about 329,000 tons of alkaline solutions, salt cakes, and sludges that contain considerable quantities of hazardous long-lived plutonium, neptunium, and americium isotopes (Delegard et al 1994). However, the waste is not homogenous; rather its chemical composition is complex and varies greatly from tank to tank.…”
Section: Introductionmentioning
confidence: 99%
“…Radioactive wastes include alkaline solutions and sludges of complex composition that have accumulated at the Hanford Site from processing irradiated nuclear materials. The wastes contain high concentrations of NaOH, NaNO,, NaNO,, organic complexants, uranium fission products, and the long-lived isotopes of neptunium, plutonium, and americium (Delegard et al 1994). …”
Section: Summary Of the Resultsmentioning
confidence: 99%
“…Alkaline radioactive wastes accumulated during military plutonium production on the Hanford Site contain NaOH, NqCO,, NaNO,, NaNO,, organic complexants, uranium fission products, and the longlived isotopes of neptunium, plutonium, and americium (Delegard et al 1994). The purification of alkaline solutions fiom neptunium, plutonium, and americium can be performed by a technique of coprecipitation of transuranium elements with carriers generated in alkaline solution by the Method of Appearing Reagents .…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus was considered to-be of secondary importance following 1 aboratory testing of the C/D process with genuine wastes (Delegard et al 1994). The laboratory work showed that, with sufficient washing, most of the phosphorus (present as phosphate) was dissolved leaving 1 ittle phosphate in the residue except that associated with alkaline earth elements such as calcium and strontium.…”
Section: Candidate Separations Processes Werementioning
confidence: 99%